РОЛЬ ХАРКІВСЬКОЇ РЕГІОНАЛЬНОЇ ЕЛІТИ У КОНСТРУЮВАННІ УКРАЇНСЬКОЇ ІДЕНТИЧНОСТІ У ПОСТРАДЯНСЬКУ ДОБУ (Zaporizhzhia Historical Review, 2021)
In the article the attention is paid to the processes of national identities formation, the Ukrainian elite creation after the getting the Ukrainian independence in 1991. The author characterizes the ways of the Ukrainian nation-making and the conditions of the state power bodies transformation because of the system, which was typical for the soviet period before the independent democratic Ukrainian state.